The administration of justice - Davis, Dennis M (2017)
In the 2004 chapter on the Administration of Justice, we took the unusual step of criticising Juta, the publisher of the Annual Survey (at 823-6). We did so because we considered that Juta had behaved improperly in publishing a judgment critical of Jeremy Gauntlett SC but refusing his request to record that the Cape Bar Council had exonerated him of improper conduct. The details of the saga are fully recorded in last year's contribution and need not be repeated. As the publisher of the Annual Survey, Juta asserted a right to respond to the criticism levelled at it (2004 Annual Survey 845). Indeed, it appropriated an entire printed page to do so. Regrettably, we believe that Juta has compounded its error and that its comments cannot be allowed to stand unchallenged. In essence, Juta makes three points. First, the judgment on leave to appeal was reported because it 'contradicted a previous assumption that a dissenting judgment in the court a quo meant that leave to appeal would be granted as a matter of course' (ibid). Second, the South African Law Reports contains only such editorial comment as may be necessary to elucidate the published judgments. Third, '[i]t is not incumbent upon the publishers of law reports to annotate the reports in order to vindicate any of the persons who from time to time draw adverse comment from presiding judges' (ibid). None of these arguments withstand scrutiny